Potential novel drug carriers for inner ear treatment: hyperbranched polylysine and lipid nanocapsules. (August 2009) - Scheper, Verena; Wolf, Melanie; Scholl, Markus; Kadlecova, Zuzana; Perrier, Thomas; Klok, Harm-Anton; Saulnier, Patrick; Lenarz, Thomas; Stööver, Timo
Aim: Treatment of sensorineural hearing loss could be advanced using novel drug carriers such as hyperbranched polylysine (HBPL) or lipid nanocapsules (LNCs). This study examined HBPL and LNCs for their cellular uptake and possible toxicity in vitro and in vivo as the first step in developing novel nanosized multifunctional carriers.Method: Having incubated HBPL and LNCs with fibroblasts, nanoparticle uptake and cell viability were determined by confocal laser scanning microscopy, fluorescence measurements and neutral red staining. In vivo, electrophysiology, confocal laser scanning microscopy and cytocochleograms were performed for nanoparticle detection and also toxicity studies after intracochlear application.Results: Both nanoparticles were detectable in the fibroblasts'' cytoplasm without causing cytotoxic effects. After in vivo application they were visualized in cochlear cells, which did not lead to a change in hearing threshold or loss of hair cells. Biocompatibility and traceability were demonstrated for HBPL and LNCs. Thus, they comply with the basic requirements for drug carriers for potential application in the inner ear.